Effects of fungal treatment on the in vitro degradation of cassava - Ramin, Mohammad; Yaakub, Halimatun; Alimon, Abdul Razak; Mohd Jelan, Zainal Aznam (Fundación CIPAV, Cali, Colombia, 2011)
The objective of this experiment was to increase the nutrient value of cassava by the solid state fermentation technique (SSF). Peeled cassava root was fermented for 10 days under solid state fermentation culture with two different fungi (Aspergillus niger and Rhizopus oryzae). A follow-up in-vitro gas production experiment was conducted in order to determine the kinetics of fermentation (degradation rate) using cassava from the two SSF. There was an increase in crude protein concentration due to treatment of cassava with A. niger but not with R. oryzae compared to the unfermented treatment (fresh cassava). Acid detergent fibre (ADF) and neutral detergent fibre (NDF) were greater for both fermented treatments compared to the unfermented treatment. The rate of fermentation, in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) were greater, and gas production was higher, from the cassava fermented with R. oryzae after 10 days SSF compared to cassava fermented for 10 days with A. niger or the unfermented cassava. It was concluded that A. niger is an effective fungus to increase the crude protein of cassava.